Baseline results from the EU28 EUROMOD: 2011-2016 - Mattia Makovec; Miko Tammik (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This paper presents baseline results from the latest version of EUROMOD (version G4.0+), the tax-benefit microsimulation model for the EU. First, we briefly report the process of updating EUROMOD. We then present indicators for income inequality and risk of poverty using EUROMOD and discuss the main reasons for differences between these and EU-SILC based indicators. We further compare EUROMOD distributional indicators across all EU 28 countries and over time between 2011 and 2016. Finally, we provide estimates of marginal effective tax rates (METR) for all 28 EU countries in order to explore the effect of tax and benefit systems on work incentives at the intensive margin. For a subset of countries for which 2014 EU-SILC data are available in EUROMOD, we also compare poverty and inequality indicators and METR across countries and over time between 2013 and 2016. Throughout the paper, we highlight both the potential of EUROMOD as a tool for policy analysis and the caveats that should be borne in mind when using it and interpreting results. This paper updates the work conducted in the EUROMOD Working Paper EM3/16.
Keywords: C15; H24; H31; H55; I3; 330; microsimulation; redistribution; tax-benefit system; poverty; inequality; work incentives